2005
DOI: 10.1590/s0103-50532005000700028
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous monitoring of toxic metals on white poplar (populus) by SWASV

Abstract: foi utilizada na determinação simultânea de quantidades traço dos metais tóxicos Pb(II), Cd(II) e Cu(II) em folhas de choupo (populus), utilizadas como bio-indicador, recolhidas numa área de tráfego automóvel intenso da cidade de Lisboa. As folhas, após secagem, foram submetidas a um processo de digestão ácida por microondas. Para a aplicação desta técnica à análise das folhas foi realizado um estudo de optimização dos vários parâmetros voltamétricos. O eletrodo de trabalho consistiu num filme de mercúrio depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…25 These values are similar to those determined in the present study, namely, 1.5−2 μg/g, 0.12− 0.14 μg/g, and 6−7.5 μg/g for Pb, Cd, and Cu, respectively. Peppermint leaves, however, were found to contain 2.41 μg/g Pb, 0.09 μg/g Cd, and 12 μg/g Cu.…”
Section: ■ Materials and Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…25 These values are similar to those determined in the present study, namely, 1.5−2 μg/g, 0.12− 0.14 μg/g, and 6−7.5 μg/g for Pb, Cd, and Cu, respectively. Peppermint leaves, however, were found to contain 2.41 μg/g Pb, 0.09 μg/g Cd, and 12 μg/g Cu.…”
Section: ■ Materials and Methodssupporting
confidence: 91%
“…Leaves of poplar analyzed in Portugal were found to have the following concentrations: 2−3 μg/g for Pb, 0.1−0.2 μg/g for Cd, and 4−5 μg/g for Cu. 25 These values are similar to those determined in the present study, namely, 1.5−2 μg/g, 0.12− 0.14 μg/g, and 6−7.5 μg/g for Pb, Cd, and Cu, respectively. Peppermint leaves, however, were found to contain 2.41 μg/g Pb, 0.09 μg/g Cd, and 12 μg/g Cu.…”
Section: ■ Materials and Methodssupporting
confidence: 91%
“…A study of poplar leaves (Portugal) obtained values of 2 to 3 µg/g for Pb, 0.1 to 0.2 µg/g for Cd, and 4 to 5 µg/g for Cu (Silva et al 2005). These results are in the same order of magnitude as those of the presented study, namely 1.5 to 2 µg/g, 0.12 to 0.14 µg/g, and 6 to 7.5 µg/g for Pb, Cd, and Cu, respectively.…”
Section: Comparison With Other Leavesmentioning
confidence: 99%
“…Numerous studies reported the poplar’s efficiency in phytoremediation and the effect of metals on the poplar’s physiological processes. Regarding the poplar’s biomonitoring capabilities, most of the research focuses on their use in soil pollution and only a few in air pollution [ 16 , 17 , 22 , 23 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%